Characterization of new microsatellite loci from the razor clam (Sinonovacula constricta) and transferability to related species. (August 2015) - Wu, Xueping; Feng, Yanwei; Ma, Haitao; Pan, Ying; Liu, Xiangquan
Abstract: Simple sequence repeats (SSRs) have been widely used in marine animals, but were seldom used directly to test intra- and inter-specific transferability in the populations of related species. 19 new pairs of microsatellite primers were obtained from Sinonovacula constricta . The allele number of these markers ranged from 3 to 15. The observed and expected heterozygosities changed from 0.033 to 1.000 and from 0.033 to 0.912, respectively. Three loci (SC3-8, SC3-19, and SC4-17) significantly deviated from Hardy–Weinberg equilibrium after Bonferroni correction, and none of the loci showed linkage disequilibrium. In addition, the transferability of all polymorphic SSRs was assessed in three closely related species. The results showed that four loci were informative in Solen strictus (SC2-11, SC2-12, SC4-19 and SC2-2) and Cultellus attenuates (SC2-2, SC4-9, SC4-19 and SC3-11), respectively, and two loci (SC2-2 and SC2-11) were informative in Solen grandis. These loci will be useful for the evaluation of genetic diversity, connectivity among related species and stock management. Highlights: 19 polymorphic markers were isolated and tested in Sinonovacula constricta . The number of alleles ranged from 3 to 15. The transferability of SSRs was assessed in three related species. Four loci were informative in Solen strictus and Cultellus attenuatus ; for Solen grandis, only two loci were informative.